2016
DOI: 10.1002/jmor.20525
|View full text |Cite
|
Sign up to set email alerts
|

Comparative data on the differentiation and growth of bone ornamentation in gnathostomes (Chordata: Vertebrata)

Abstract: Bone ornamentation, in the form of rounded pits framed by a network of ridges, is a frequent feature among a great diversity of gnathostome taxa. However, the basic osteogenic processes controlling the differentiation and development of these reliefs remain controversial. The present study is a broad comparative survey of this question with the classical methods used in hard tissue histology and paleohistology. Distinct processes, unevenly distributed among taxa, are involved in the creation and growth of pits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 76 publications
1
26
1
2
Order By: Relevance
“…De Buffrénil et al (2016) observed six main patterns of such modification. The simplest one is repetition of the width or position of pits and ridges from one growth stage to the following one.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…De Buffrénil et al (2016) observed six main patterns of such modification. The simplest one is repetition of the width or position of pits and ridges from one growth stage to the following one.…”
Section: Discussionmentioning
confidence: 98%
“…Although dermal sculpture was early recognized as a characteristic of basal tetrapods (e.g., Von Meyer, 1858; Fraas, 1889; Fritsch, 1889; Zittel, 1911), the morphogenesis of the sculptures is still an open question (summarized by Witzmann 2009; Witzmann et al 2010; De Buffrénil et al 2016). Among extant tetrapods, growth of dermal bony tubercles and ridges has been studied in osteoderms of squamates and in dermal skull bones and osteoderms of crocodiles.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations